Estudo geoquímico e geocronológico Rb-Sr e Sm-Nd em zonas de cisalhamento mineralizadas em ouro e suas relações com as rochas encaixantes e geocronológico Sm-Nd em mineralizações de scheelita na faixa Seridó - Trindade, Ivaldo Rodrigues da (2000)
Great part of the gold mineralizations are associated with shearing zones through which circulate a great volume of fluids, that interact with the host rocks, originating leaching or precipitation of chemical elements, including gold. The studied mineralizations are inserted in the Seridó Belt. The tungsten mineralization in Brejuí Mine is hosted in calcsilicate rocks from Jucurutu Formation. The São Francisco auriferous mineralization has as host rocks mica-schists from Seridó Formation, while the Ponta da Serra and Fazenda Simpático mineralizations are hosted in orthogneisses of this fold belt basement. The research conducted on these mineralizations had the purpose of integrate the data of chemical elements behavior during the shearing/mineralizing event, and its influence on the isotopic systems Rb-Sr and Sm-Nd. The studies of chemical mobility in the auriferous mineralizations showed that elements that during the shearing displayed in general an immobile behavior were Al, Ti and Zr. Among the elements that were mobilized during the event, K and Rb showed mass gain in ali belts of transformed rocks, while the elements Ca, Na and Sr normally lost mass. Petrographic studies showed that the minerais biotite and plagioclase, in all investigated mineralizations, played an important role in the chemical reactions occurred in the transformed rocks to the generation of muscovite, cordierite and sillimanite, justifying the input of K to the formation of muscovite, and the release of Na and Ca from plagioclase to the fluid phase. In the São Francisco auriferous mineralization, the results of the Rb-Sr isotopic analysis yielded ages of 645 ± 19 Ma and 596 ± 17 Ma, with both samples, from original and transformed rocks. Two ages, 569 ± 20 Ma. and 554 ± 19 Ma., were obtained with samples frem the transformed rocks domain. These ages suggest that there were two metamorphic pulses during the emplacement of the mineralized shearing zone. The Sm-Nd data yielded TDM ages of 1,31 Ga and 1,26 Ga with 3Nd (0,6 Ga) of -0,26 e -0,40 for the original and final transformed rocks, respectively. In case of the orthogneisses of Caicó Complex, e.g. the Ponta da Serra and Fazenda Simpático mineralizations, the Rb-Sr data did not yield ages with geological significance. In the Ponta da Serra mineralization, the Sm-Nd isotopic data yielded T DM ages of 2,56 Ga and 2,63 Ga to the original rocks and of 2,71 Ga to the mineralized sheared rock, and values of 3Nd (2,0 Ga) between -3,70 e -5,42 to the original and sheared rock, respectively. In the Fazenda Simpático, Sm-Nd data yielded TDM between 2,65 and 2,69 Ga with values of 3Nd (2,0 Ga) between -5,25 e -5,52. Considering the Sm-Nd data, the TDM ages may be admitted as the age of the parental magma extraction, producer of the protoliths of the orthogneisses from Ponta da Serra and Fazenda Simpático mineralizations. The chemical mobility studies showed that in the basement hosted mineralizations, Rb achieved mass while Sr lost mass, as Sm as well as Nd were strongly mobilized. The Sm/Nd ratio remained constant, however, confirming the isochemical character of those elements. In the basement mineralizations, Rb-Sr ages are destituted of geological significance, because of the partial opening of the isotopic system during the tectono-metamorphic transformations. In the tungsten mineralization, the diagram Sm-Nd constructed with the whole-rock data of calcsilicatic and the high-temperature paragenesis (garnet, diopside and iron-pargasitic hornblende) indicated an 631 ± 24 Ma age, while with the whole-rock data and low-temperature paragenesis (vesuvianite, epidote and calcite), a 537 ± 107 Ma age was obtained. These ages, associated with the petrographic observations, suggest that there was a time gap among the hydrothernal events responsible by the formation of the high and low temperature paragenesis in the calcsilicatic rocks mineralized in scheelite